Combined and progestagen-only hormonal contraceptives and breast cancer risk: A UK nested case-control study and meta-analysis. - Danielle Fitzpatrick; Kirstin Pirie; Gillian Reeves; Jane Green; Valerie Beral (PLoS Medicine)
Background Current or recent use of combined oral contraceptives (containing oestrogen+progestagen) has been associated with a small increase in breast cancer risk. Progestagen-only contraceptive use is increasing, but information on associated risks is limited. We aimed to assess breast cancer risk associated with current or recent use of different types of hormonal contraceptives in premenopausal women, with particular emphasis on progestagen-only preparations. Methods and findings Hormonal contraceptive prescriptions recorded prospectively in a UK primary care database (Clinical Practice Research Datalink [CPRD]) were compared in a nested case-control study for 9,498 women aged <50 years with incident invasive breast cancer diagnosed in 1996 to 2017, and for 18,171 closely matched controls. On average, 7.3 (standard deviation [SD] 4.6) years of clinical records were available for each case and their matched controls prior to the date of diagnosis. Conditional logistic regression yielded odds ratios (ORs) and 95% confidence intervals (CIs) of breast cancer by the hormonal contraceptive type last prescribed, controlled for age, GP practice, body mass index, number of recorded births, time since last birth, and alcohol intake. MEDLINE and Embase were searched for observational studies published between 01 January 1995 and 01 November 2022 that reported on the association between current or recent progestagen-only contraceptive use and breast cancer risk in premenopausal women. Fixed effects meta-analyses combined the CPRD results with previously published results from 12 observational studies for progestagen-only preparations. Overall, 44% (4,195/9,498) of women with breast cancer and 39% (7,092/18,171) of matched controls had a hormonal contraceptive prescription an average of 3.1 (SD 3.7) years before breast cancer diagnosis (or equivalent date for controls). About half the prescriptions were for progestagen-only preparations. Breast cancer ORs were similarly and significantly raised if the last hormonal contraceptive prescription was for oral combined, oral progestagen-only, injected progestagen, or progestagen-releasing intrauterine devices (IUDs): ORs = 1.23 (95% CI [1.14 to 1.32]; p < 0.001), 1.26 (95% CI [1.16 to 1.37]; p < 0.001), 1.25 (95% CI [1.07 to 1.45]; p = 0.004), and 1.32 (95% CI [1.17 to 1.49]; p < 0.001), respectively. Our meta-analyses yielded significantly raised relative risks (RRs) for current or recent use of progestagen-only contraceptives: oral = 1.29 (95% CI [1.21 to 1.37]; heterogeneity χ25 = 6.7; p = 0.2), injected = 1.18 (95% CI [1.07 to 1.30]; heterogeneity χ28 = 22.5; p = 0.004), implanted = 1.28 (95% CI [1.08 to 1.51]; heterogeneity χ23 = 7.3; p = 0.06), and IUDs = 1.21 (95% CI [1.14 to 1.28]; heterogeneity χ24 = 7.9; p = 0.1). When the CPRD results were combined with those from previous published findings (which included women from a wider age range), the resulting 15-year absolute excess risk associated with 5 years use of oral combined or progestagen-only contraceptives in high-income countries was estimated at: 8 per 100,000 users from age 16 to 20 years and 265 per 100,000 users from age 35 to 39 years. The main limitation of the study design was that, due to the nature of the CPRD data and most other prescription databases, information on contraceptive use was recorded during a defined period only, with information before entry into the database generally being unavailable. This means that although our findings provide evidence about the short-term associations between hormonal contraceptives and breast cancer risk, they do not provide information regarding longer-term associations, or the impact of total duration of contraceptive use on breast cancer risk. Conclusions This study provides important new evidence that current or recent use of progestagen-only contraceptives is associated with a slight increase in breast cancer risk, which does not appear to vary by mode of delivery, and is similar in magnitude to that associated with combined hormonal contraceptives. Given that the underlying risk of breast cancer increases with advancing age, the absolute excess risk associated with use of either type of oral contraceptive is estimated to be smaller in women who use it at younger rather than at older ages. Such risks need be balanced against the benefits of using contraceptives during the childbearing years.